2017
DOI: 10.1002/bab.1509
|View full text |Cite
|
Sign up to set email alerts
|

Valorization of antioxidants extracted from olive mill wastewater

Abstract: Antioxidants are highly important gradients used to preserve cosmetic products and reduce the effect of oxidative stress on the skin. The present work explores the possibility of using phenolic compounds of olive mill wastewater (OMW) as effective alternatives to the commercial antioxidants used in cosmetic formulations deemed by their allergic and carcinogenic effects. Esterification of tyrosol and hydroxytyrosol extracted from OMW with various fatty acids was conducted using Novozyme 435 lipase as a biocatal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 44 publications
1
19
0
Order By: Relevance
“…These results demonstrate the strong capacity of the fraction F5 to inhibit Campylobacter growth. According to the described results, recent studies have also demonstrated the antibacterial effects of phenolic and secoiridoid enriched fractions obtained from OMW on several bacterial pathogens, including gram positive and gram negative bacteria (Aissa et al, 2017;Belaqziz et al, 2017). Usually, the antibacterial effect is greater in grampositive than gram-negative bacteria, which is consistent with a thicker and more complex cell wall in the case of gram-negative bacteria (Leouifoudi et al, 2015;Obied et al, 2007).…”
Section: Accepted Manuscriptsupporting
confidence: 59%
“…These results demonstrate the strong capacity of the fraction F5 to inhibit Campylobacter growth. According to the described results, recent studies have also demonstrated the antibacterial effects of phenolic and secoiridoid enriched fractions obtained from OMW on several bacterial pathogens, including gram positive and gram negative bacteria (Aissa et al, 2017;Belaqziz et al, 2017). Usually, the antibacterial effect is greater in grampositive than gram-negative bacteria, which is consistent with a thicker and more complex cell wall in the case of gram-negative bacteria (Leouifoudi et al, 2015;Obied et al, 2007).…”
Section: Accepted Manuscriptsupporting
confidence: 59%
“…For example, es-terification of tyrosol and hydroxytyrosol extracted from olive mill wastewater with various fatty acids (caprate, laurate, and palmitate) catalyzed by N435 was successfully performed and shown to be efficient to avoid lipid oxidation. 434 3.2.4. Interesterification of glycerides.…”
Section: Food Technology: Glyceride Modifications and Productionmentioning
confidence: 99%
“…The detected PCs are generally recognized as potent antioxidants [59], antibacterial (gram positive and gram negative), antifungal, and have demonstrated activities against yeast [60]. Their industrial application for these properties are increasing, both in the food industry, as reported for hydroxytyrosol and verbascoside in meat preparation [59,61], or olive leaf phenolics in dairy preparation [62] and OMW extract for olive oil preservation [60], as well as in the cosmetic industries, as reported for oleuropein used as antiaging ingredient in cosmetic formulations [63].…”
Section: Desorption / Regeneration Tests and Desorbed Product Charactmentioning
confidence: 99%